“Right diet for the right person”: a focus group study of nutritionist-dietitians’ perspectives on nutritional genomics and gene-based nutrition advice - Jacus S. Nacis; Marilou R. Galang; Jason Paolo H. Labrador; Milflor S. Gonzales; Aurora Maria Francesca D. Dablo; Diana Glades A. Domalanta-Ronquillo; Victor Franco J. Alfonso; Idelia G. Glorioso; Marietta P. Rodriguez (Journal of Community Genetics, 2022)
Advances in nutritional genomics are intended to revolutionize nutrition practice. A basic understanding of nutritional genomics among nutritionist-dietitians is critical for such advancements to occur. As a precedent to the development and integration of gene-based nutrition advice, this study aimed to assess hospital-based nutritionist-dietitians’ perceptions of nutritional genomics. A total of ten focus group discussions (FGDs) with sixty-one registered nutritionist-dietitians (RNDs) from hospitals in the National Capital Region (NCR), Philippines, were conducted from October to November 2019. Data were collected using a pretested semistructured discussion guide, and thematic analysis was subsequently performed. Diverging perceptions about nutritional genomics were noted among the FGD participants. Five themes emerged relating to the enablers and barriers of gene-based nutrition advice: training and capacity building, the extent of information to be disclosed, cost, ethical considerations, and government support. Themes related to the desired features of the gene-based nutrition advice included being consent-driven, cost-effective, technology-oriented, and guided by standards. The results of this study suggest that training and continued learning will equip RNDs to provide nutrition advice based on genetic information. However, other factors, such as cost and ethical considerations, are critical dimensions that need to be acknowledged and addressed before integrating gene-based advice into nutrition practice.

The strength of integrin binding between neutrophils and endothelial cells - V. Labrador; P. Riha; S. Muller; D. Dumas; X. Wang; J. F. Stoltz (European Biophysics Journal, 2003)

The effect ofin vitro fluoride ion treatment on the ultrasonic properties of cortical bone - W. R. Walsh; D. P. Labrador; H. D. Kim; N. Guzelsu (Annals of Biomedical Engineering, 1994)